Gold nanoparticle-loaded macrophages enhance radiotherapy via immune remodeling in oral cancer - Hui-Wen Chan; Pei-Wei Sheung; Stella Tzu-Ming Tsao; Chun-Yi Wu; Hui-Yen Chuang (Materials Today Bio, 2025)
Gold nanoparticles (GNPs) are promising radiosensitizers owing to their high atomic number, but their therapeutic efficacy is often limited by reticuloendothelial system (RES)-mediated clearance and poor tumor accumulation attributable to elevated interstitial fluid pressure. This study explored macrophage-mediated GNP delivery to enhance radiotherapy (RT) efficacy in oral cancer by leveraging the tumor-homing ability, immune plasticity, hypoxia tropism, and RES evasiveness of macrophages. Murine oral cancer cells (MCTQ1) and macrophages (RAW 264.7) were used. GNPs were synthesized using the Turkevich method, which were then assessed for radiosensitization using cell viability and colony formation assays. GNPs were radiolabeled with Iodine-131 (131I) using the chloramine-T method, and uptake by RAW 264.7 cells was quantified at various time points to optimize the generation of GNP-loaded macrophages (GNP@Rs). MTCQ1 tumor-bearing mice were divided into control, RT, GNP, RAW, GNP + RT, RAW + RT, and GNP@R + RT groups. Tumor volumes were monitored after GNP or cell administration and/or RT (8 Gy). Flow cytometry was used to analyze the immune cell populations post-treatment. Transwell assays confirmed that GNP loading did not impair macrophage migration, and in vivo fluorescence imaging demonstrated strong tumor tropism of RAW 264.7 cells and GNP@Rs. GNP@Rs maintained their migration ability and exhibited robust tumor accumulation for up to 96 h. Notably, GNP@R + RT treatment significantly enhanced tumor suppression relative to RT alone and increased the infiltration of macrophages, activated dendritic cells, CD4+ and CD8+ T cells, and natural killer cells. Macrophage-mediated GNP delivery successfully improved RT outcomes in oral cancer by increasing radiosensitivity and modulating immune microenvironment.